The Impact Of Practical Education Programs On Raising The Level Of Soft Skills Among Female Students: A Prospective Study (Journal of Namibian Studies : History Politics Culture, 2023)
Soft skills are essential for future students. This study aimed to find out the impact of the practical education program in raising the level of soft skills for female students at King Faisal University. The study adopted the observational tool as a data collection tool for this study. The study population consisted of 300 students of the College of Education in different specializations from kindergarten, educational techniques and art education in the first semester of the academic year 1443-1444 AH, and 100 cooperating teachers from public education schools affiliated to the Al-Ahsa Education Department, and kindergartens affiliated to the Kindergarten Supervision Department. The study included all members of the study population. The results of the study showed that there are several soft skills that are necessary for training the student teacher. There are statistically significant differences between the mean scores of the pre and post observations of the practice of the experimental study group of practical education students for all soft skills. Also I the result  that there is a statistically significant difference at the level (α ≤ 0.01) between the mean scores of the pre and post observations for the practice of the experimental study group of practical education students for all soft skills.